Mustang the American muscle car - Wright, Nicky (Broomall, PA Mason Crest, 2018)
Tells how Mustang was born and has grown to thunder around the world.
The tale from the little black book -- The end of the beginning, and the beginning of the end -- Wow! That's something else -- The pony gallops into the new millenium.
Includes bibliographical references (page 93) and index.
8 - 12 years
105958
Keywords: Mustang automobile -- Pictorial works -- Juvenile literature; Juvenile works; Pictorial works